Oral Presentations Abstracts: THE EMBASSY OF GOOD SCIENCE: A COMMUNITY-BASED INITIATIVE TO STRENGTHEN RESEARCH INTEGRITY AND ETHICS - EVANS, Natalie; INGUAGGIATO, Giulia; VAN HOOF, Marc; GORDIJN, Bert; DIERICKX, Kris; MARUSIC, Ana; WIDDERSHOVEN, Guy (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 The areas of Research Ethics and Research Integrity (RE+RI) are rapidly evolving. Guidelines, standards, and laws have been drafted in many countries, regions and institutions. However, the regulatory proliferation does not necessarily yield clear guidance for practice: researchers often lack up-to-date and easily accessible information and guidance on how to apply principles and norms. The same is true for RE+RI evaluation committees, who lack easy access to case studies. The Embassy of Good Science is an online initiative to address these problems. The Semantic MediaWiki platform brings together, and makes smart connections between, relevant guidelines and regulations, cases and scenarios, and teaching materials. The platform provides practical information about how to apply norms and principles in every day practice and how to teach about them. For example, The Embassy contains cases and scenarios on researchers’ day-to-day dilemmas, a discussion forum where researchers can share experiences, and easily adaptable teaching resources. Developed in consultation with stakeholders, the Embassy is managed by the European funded EnTIRE project. The initial content has been gathered via systematic reviews and is continually added to and updated by users. In the long-term, The Embassy will be community-owned and sustainable. The Embassy primarily supports researchers and RE+RI committee members. The platform also presents the opportunity to compare RE+RI principles, norms and practices worldwide, facilitating mutual learning and making the diversity of the RE+RI regulatory framework apparent. In this session, we will describe and demonstrate The Embassy’s value for practice, education and policy.